PENGARUH PERSENTASE PENDUDUK MISKIN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) PADA KABUPATEN BERAU: PENGARUH PERSENTASE PENDUDUK MISKIN DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) PADA KABUPATEN BERAU - Agus Purwoko (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
This study aims to examine the effect of the percentage of poor population and economic growth on the Human Development Index (HDI) in Berau Regency. Based on the results of the study, firstly, the percentage of poor people has no influence on the HDI in Berau Regency. Second, economic growth has a significant effect on the HDI in Berau Regency. From the results of the analysis of the coefficient of determination R Square known 52.7%. This shows the influence of the variable Percentage of Poor Population (X1) and the variable Economic Growth (X2) of 52.7% while 47.3% is influenced by other variables not included in this study.